Electrocatalysis of Palladium Nanoparticles on Rough Graphite Electrodes Towards Hydrogen Evolution Reaction - Martina Schwager; Constanze Eulenkamp; Jenni Richter (Advanced Energy Conversion Materials, 2025)
The electrocatalytic performance of palladium nanoparticles (PdNPs) supported on rough graphite for the hydrogen evolution reaction (HER) was investigated. Chronopotentiometric deposition resulted in a homogeneous distribution of PdNPs across the substrate surface. Electrochemical analysis of electrodes with varying Pd loadings demonstrated that HER proceeds via the Volmer-Heyrovsky mechanism, with a loading of 43 µg/cm2 achieving notable catalytic performance. Impedance spectroscopy revealed that the experimental data are accurately described by a two-time-constant parallel equivalent circuit model. At this optimal loading, mass transfer resistance was markedly reduced, particularly at high overpotentials. Under these conditions, charge transfer resistance became the dominant factor influencing HER activity, highlighting the importance of loading-dependent kinetics in optimizing catalytic performance.